2015
DOI: 10.1186/s12870-015-0480-y
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive sequence analysis and karyotyping reveals centromere-associated DNA sequences in radish (Raphanus sativus L.)

Abstract: BackgroundRadish (Raphanus sativus L., 2n = 2x = 18) is a major root vegetable crop especially in eastern Asia. Radish root contains various nutritions which play an important role in strengthening immunity. Repetitive elements are primary components of the genomic sequence and the most important factors in genome size variations in higher eukaryotes. To date, studies about repetitive elements of radish are still limited. To better understand genome structure of radish, we undertook a study to evaluate the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 50 publications
(66 reference statements)
2
40
0
Order By: Relevance
“…Usually, centromeric DNA sequences in plant species consist of species-specific tandem repeats and retrotransposons, and these sequences are located on all centromeric regions (Zhong et al, 2002 ; Nagaki et al, 2003 , 2009 , 2011 ; Nagaki and Murata, 2005 ; Houben et al, 2007 ; Tek et al, 2010 , 2011 ; Wang et al, 2011 ; Neumann et al, 2012 ; He et al, 2015 ). In this study of sunflower, we identified two types of centromeric DNA sequences (Supplementary Table 2 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, centromeric DNA sequences in plant species consist of species-specific tandem repeats and retrotransposons, and these sequences are located on all centromeric regions (Zhong et al, 2002 ; Nagaki et al, 2003 , 2009 , 2011 ; Nagaki and Murata, 2005 ; Houben et al, 2007 ; Tek et al, 2010 , 2011 ; Wang et al, 2011 ; Neumann et al, 2012 ; He et al, 2015 ). In this study of sunflower, we identified two types of centromeric DNA sequences (Supplementary Table 2 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the constitutive proteins of kinetochores, centromere-specific histone H3 (CENH3) acts as a base for assembling other kinetochore proteins, and its presence epigenetically determines the kinetochore position (Perpelescu and Fukagawa, 2011 ). The first identified CENH3 was CENP-A in humans (Earnshaw and Rothfield, 1985 ), and its orthologs have been isolated from 11 of 63 APG III orders, including Poales, Asparagales, Rosales, Fabales, Malpighiales, Malvales, Brassicales, Myrtales, Solanales, Asterales, and Apiales, in this decade (Talbert et al, 2002 ; Zhong et al, 2002 ; Nagaki et al, 2004 , 2005 , 2012b ; Nagaki and Murata, 2005 ; Sanei et al, 2011 ; Wang et al, 2011 ; Neumann et al, 2012 , 2015 ; Dunemann et al, 2014 ; Masonbrink et al, 2014 ; He et al, 2015 ; Maheshawari, 2015 ). However, no CENH3 has been isolated from Asterales species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6C). Many studies have shown that satellite DNAs comprising head-to-tail tandem repeats are believed to be the most dynamic components (Biscotti et al 2015;Cai et al 2014;He et al 2015), undergoing the most rapid changes in the number and position of sites within a short evolutionary period (Mehrotra and Goyal 2014). It may also explain the largest number of E. arundinaceus-speci c sequences from the SSH library.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these sequences are probably involved in the structural and functional organization of the centromere [Padeganeh et al, 2013;He et al, 2015;Padeken et al, 2015;Steiner and Henikoff, 2015].…”
mentioning
confidence: 99%